Carbon Nanotubes: Photon‐Pair Generation with a 100 nm Thick Carbon Nanotube Film (Adv. Mater. 24/2017). Issue 24 (June 2017) - Lee, Kim Fook; Tian, Ying; Yang, He; Mustonen, Kimmo; Martinez, Amos; Dai, Qing; Kauppinen, Esko I.; Malowicki, John; Kumar, Prem; Sun, Zhipei
Abstract : The performance of nonlinear optical devices is largely limited by the small nonlinear coefficient of traditional optical materials. In article number1605978, Kim Fook Lee, Zhipei Sun, and co‐workers report a nanoscale nonlinear optical device for efficient generation of photon pairs. They design an optical device based on a 100‐nm‐thick carbon nanotube film, which is 1000 times thinner than the current existing devices, achieved through careful control of the nanotube diameter to significantly enhance the optical nonlinearity.